Extracellular Antigens from Listeria monocytogenes I. Purification and Resolution of Hemolytic and Lipolytic Antigens from Culture Filtrates of Listeria monocytogenes - Jenkins, E. M. (1971)
Two antigens were purified from culture filtrates of Listeria monocytogenes 7973 by the following procedure: (i) acid precipitation with 4 n HCl at pH 3.7, (ii) Sephadex G-75 column fractionation, (iii) diethylaminoethyl-Sephadex A50 batchwise adsorption, and (iv) rechromatography on Sephadex G-75. This procedure resulted in the resolution of two distinct antigens. One antigen, designated a hemolytic antigen because of its ability to lyse erythrocytes from a variety of species, had a specific activity of 25,000 units/mg of protein and an estimated molecular weight of at least 171,000. The other antigen, designated a lipolytic antigen because of its ability to hydrolyze egg yolk saline substrate, had a specific activity of 400 units/mg of protein and an estimated molecular weight of 52,500.